PENGARUH BUDAYA ORGANISASI TERHADAP PERKEMBANGAN PROFESIONALISME GURU SERTA DAMPAKNYA PADA KUALITAS PENDIDIKAN AGAMA ISLAM - Aidatul, Aidatul (JURNAL AL-QAYYIMAH, 2024)
This research aims to determine the influence of organizational culture on the development of teacher professionalism at Mts Yapdi. This research uses a qualitative approach through field observations and interviews. The research results show that organizational culture has a significant influence on the development of teacher professionalism at Mts Yapdi. A positive organizational culture can increase motivation, student learning achievement, job satisfaction and teacher professionalism. These results indicate that organizational culture is very important in improving teacher professionalism and teacher performance at Mts Yapdi.Â Keywords: Influence, Cultural Organization, Teacher Professionalism